The Constitutional and Legal Basis of National Human Rights Institutions in Iraq and their Compatibility with International Standards - Fayath, Hussein; Adil, Musadak (Journal of Legal Sciences, 2022)
The issue of human rights has become an international obligation of States, and the mere recognition of these rights by States, no matter how clear and precise, does not constitute a guarantee in itself. The state shall assume its status to respect human rights and fundamental freedoms. The national protection mechanisms are diverse. They are either constitutional, judicial or political. Human rights in Iraq, as each institution or body to be able to exercise its powers, must be based on a legislative basis, whether legal or constitutional basis, In order to achieve its goal of promoting and protecting human rights.